2019
DOI: 10.1080/1828051x.2019.1645624
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of a commercial diet with raw meat complemented with vegetable foods containing chickpeas or peas affects faecal microbiome in healthy dogs

Abstract: The aim of the study was to investigate if the inclusion of chickpeas or peas in the diet can modify faecal microbiome in dogs. Eight healthy adult Border collie, fed a commercial extruded diet as reference diet (RD), were divided in two groups of four individuals. At the beginning of the trial, one group received a diet based mainly of raw meat, rice and chickpeas (CP) and in the other group this pulse was substituted with peas (PE). After 14 days, the dogs with CP diet shifted to the PE and those with PE shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 37 publications
5
21
1
Order By: Relevance
“…The PCoAs of Fig 1 indicated that the factors diets and sex had an influence on the beta diversity of gut microbiome, even though a large individual variability was observed. Several studies have pointed out the high variations of faecal microbial communities in healthy dogs [13], suggesting that gut microbiome can be considered an individual fingerprint [20]. However, is not clear if this depend upon the genetic background of the host (nature) or if the environment in a broad sense (nurture) has a prevailing role in shaping the gut microbiome [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PCoAs of Fig 1 indicated that the factors diets and sex had an influence on the beta diversity of gut microbiome, even though a large individual variability was observed. Several studies have pointed out the high variations of faecal microbial communities in healthy dogs [13], suggesting that gut microbiome can be considered an individual fingerprint [20]. However, is not clear if this depend upon the genetic background of the host (nature) or if the environment in a broad sense (nurture) has a prevailing role in shaping the gut microbiome [21].…”
Section: Discussionmentioning
confidence: 99%
“…The annotates sequences from each sample and each taxonomic level were normalized to ‰ abundance profiles, already known as Relative Abundance (RA). Within each DIS, taxa with RA lower than 1‰ in more than half of the samples were excluded from the statistical analysis [13]. Beta diversity was evaluated with the phylogeny based on UniFrac [18] distance metric and visualized using Principal Coordinate Analysis (PCoA) plots.…”
Section: Computation and Statistical Analysismentioning
confidence: 99%
“…Moreover, it has been reported that there is a relationship between the low biodiversity of intestinal microbiota and high microbial fitness, with subsequent unhealthy eating behavior and obesity of the subjects [37]. In healthy dogs, as those recruited for this study, changes of biodiversity can be probably detected when the variation of nutrients supplied with the diet is relevant [22].…”
Section: Discussionmentioning
confidence: 92%
“…The 16S rRNA annotated sequences were normalized to % abundance profiles for each sample and each taxonomic level. Taxa with relative abundance lower than 10% [22][23][24] in more than half of the samples were excluded from the statistical analysis. The average percentage of reads excluded was 1.9%.…”
Section: Computation and Statistical Analysismentioning
confidence: 99%
“…Thereupon, it has been recommended that diets for diabetic dogs must be moderate to low in fat [21], since it may minimize plasmatic lipid concentrations; and high fiber content since it may lead to a decrease in blood glucose levels [22][23][24][25]. However, there is evidence suggesting that the low-fat and high-fiber combination has side effects such as deficient weight gain, bulk and softened feces, flatulence, constipation, vomit, opaque hair and lesser palatability [21][22][23][24][25][26], probably due to the effect of dietary fiber on dog microbiota [27]. Therefore, new strategies should be investigated to improve diet design for diabetic dogs.…”
Section: Introductionmentioning
confidence: 99%